Efektifitas intervensi slow stroke back massage terhadap pasien stroke hemoragik - Nusyaibah, Fathunnisa Imarah; Lengga, Vivop Marti (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Hemorrhagic stroke is a stroke that occurs due to bleeding in the brain due to blood vessel damage. Hypertension is the main risk factor for hemorrhagic stroke. The nursing diagnosis that emerged was